The Methodology of Research on Changes in Degrees of Freedom in a Balance Task - Saeed Arsham; Farzam Farahman; Fazlolah Bagheradeh; Elahe Arab ameri; Anoushirvan Kazemnejad (University of Tehran, 2009)
The aim of the present study was to introduce the methods to extract and to interpret cinematic data in order to explain movement pattern changes via joint coupling and freezing/freeing phenomena in a healthy right-dominant college male (age:26, height: 172 cm, weight: 80 kg) who practiced balance maintenance on a stabilometer. Data were gathered using a three-dimensional registration system which consisted of three cameras and a computer program (Sharif Motion Analyzer-SMA) in MATLAB software and measured the position of 19 passive markers located on subject's limbs and stabilometer. Before each trial, the system was calibrated by a metal frame of known dimensions to transform the two-dimensional camera detector values to real three-dimensional coordinates. Then, the following variables were calculated for the first, fifth and ninth trail from a 3(session) × 3(trail) course of practice: 1) stabilometer variability as a performance index; 2) absolute and relative variability of joint angles to evaluate possible freezing-freeing process; 3) cross-correlations between the angular time series in order to evaluate the presence of joint coupling. Finally, the interpretation method to extract variables was presented and some limits of such studies regarding the variability in degrees of freedom were provided.